2013
DOI: 10.1016/j.gca.2012.12.040
|View full text |Cite
|
Sign up to set email alerts
|

Annual cycle of humic substances in a temperate estuarine system affected by agricultural practices

Abstract: , et al.. Annual cycle of humic substances in a temperate estuarine system affected by agricultural practices. Geochimica et Cosmochimica Acta, Elsevier, 2013Elsevier, , 106, pp.231-246. 10.1016Elsevier, /j.gca.2012 Annual cycle of humic substances in a temperate estuarine system affected by agricultural practices AbstractAlthough widely studied for their chemical structures and properties (e.g., metal complexation, growth stimulation of planktonic species), humic substances (HS) have been very poorly quant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 100 publications
0
12
0
Order By: Relevance
“…Humic substances, predominantly formed by the breakdown of terrestrially derived organic matter, dominate as a major carbon fraction in freshwater DOM (Dittmar and Kattner, 2003). They may account for over 80 % of DOC leaching from agricultural soils, depending on the prevailing hydrological conditions (Waeles et al, 2013). Such humic substances are generally resistant to biodegradation in estuaries and the greatest changes in their quality and degradation only take place once they reach fully marine conditions (Kisand et al, 2013).…”
Section: Impact Of Dom Quality To Bgementioning
confidence: 99%
“…Humic substances, predominantly formed by the breakdown of terrestrially derived organic matter, dominate as a major carbon fraction in freshwater DOM (Dittmar and Kattner, 2003). They may account for over 80 % of DOC leaching from agricultural soils, depending on the prevailing hydrological conditions (Waeles et al, 2013). Such humic substances are generally resistant to biodegradation in estuaries and the greatest changes in their quality and degradation only take place once they reach fully marine conditions (Kisand et al, 2013).…”
Section: Impact Of Dom Quality To Bgementioning
confidence: 99%
“…Skrabal et al (2000) have however proposed that they could correspond to biogenic compounds (exudates from bacteria/macrofauna or microbial metabolites), or to the alteration of pre-existing organic substances. The fact that HS behave conservatively in our system (Waeles et al, 2013), even in spring, is more in favor of a biotic nature for these compounds. More specific work is needed for describing sediment-porewater exchanges of Cu species in estuarine areas of preferential sedimentation of the continental OM.…”
Section: Spring Cu Additions In the Lower Part Of The Systemmentioning
confidence: 74%
“…Guo and Santschi, 2007). In the Penzé system we showed that humic substances which accounted for a high proportion of DOC were mainly observed as colloidal species (Waeles et al, 2013). Their control on Cu concentration and Cu colloidal distribution is discussed below.…”
Section: Importance Of the Cu Colloidal Fraction; Comparison With Othmentioning
confidence: 82%
See 2 more Smart Citations